The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1007/s00125-019-05017-2
|View full text |Cite
|
Sign up to set email alerts
|

Higher circulating omentin is associated with increased risk of primary cardiovascular events in individuals with diabetes

Abstract: Aims/hypothesis Higher concentrations of the adipokine omentin are associated with lower levels of cardiometabolic risk factors in experimental and cross-sectional studies, but with higher risk of type 2 diabetes and cardiovascular diseases in population-based cohort studies. However, it is unknown whether high omentin concentrations are associated with increased risk of cardiovascular events in people with established diabetes. Therefore, the present study investigated the association between serum omentin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
(78 reference statements)
2
23
0
Order By: Relevance
“…The European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam study showed that higher levels of omentin-1 were related to an increased risk of stroke in metabolically healthy participants ( Menzel et al, 2016 ). Recent 14 years of follow-up in a prospective study on diabetes without a previous cardiovascular event showed that higher omentin-1 concentrations are associated with a higher risk for CVD events, incidence of primary stroke, and incidence of cardiovascular death even after adjustment for cardiovascular risk factors ( Niersmann et al, 2020 ). As mentioned above, a highly heterogeneous association between omentin-1 and CMD has been reported.…”
Section: Omentin-1mentioning
confidence: 99%
“…The European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam study showed that higher levels of omentin-1 were related to an increased risk of stroke in metabolically healthy participants ( Menzel et al, 2016 ). Recent 14 years of follow-up in a prospective study on diabetes without a previous cardiovascular event showed that higher omentin-1 concentrations are associated with a higher risk for CVD events, incidence of primary stroke, and incidence of cardiovascular death even after adjustment for cardiovascular risk factors ( Niersmann et al, 2020 ). As mentioned above, a highly heterogeneous association between omentin-1 and CMD has been reported.…”
Section: Omentin-1mentioning
confidence: 99%
“…Omentin-1, a newly identified adipokine in human visceral omental adipose tissue, is extensively involved in the regulation and maintenance of a wide variety of physiological and pathological processes, including insulin sensitivity, energy expenditure, blood pressure, glycolipid metabolism, inflammatory response, neuroendocrine activity, immunity, homeostasis, angiogenesis, endothelial and cardiovascular function, reproduction, and recently bone metabolism [ 6 , 7 , 11 ]. In the present study, we firstly found that T2DM patients with osteoporosis had significantly higher circulating omentin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating omentin-1 was associated with inflammatory disease, obesity, IR, diabetes and diabetic vascular complications, hypertension, hyperlipidemia, metabolic syndrome, polycystic ovary syndrome, obstructive sleep apnea syndrome, chronic obstructive pulmonary disease, endothelial dysfunction, and atherosclerosis and related cardiovascular diseases such as ischemic heart disease [ 6 – 11 ], all of which have been proposed to be implicated in the pathogenesis of osteoporosis [ 3 , 12 , 13 ]. Moreover, it has been reported that serum omentin-1 inversely correlates with leptin and positively correlates with adiponectin and vitamin D [ 7 , 9 , 14 ], whereas the abovementioned cytokines have also been suggested to be involved in bone metabolism [ 14 ]. Thus, we postulated that omentin-1 may be associated with the regulation of bone metabolism and might play a pivotal role in the pathogenesis of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to an inadequate upregulation of omentin level in response to stimuli that raise the cardiovascular risk in patients with diabetes. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%